An Empirical Evidence of Dynamic Interaction between Institutional Fund Flows and Stock Market Returns in India - Naik, Pramod Kumar; Padhi, Puja (Indian Journal of Finance, 2015)
This study examined the relationship between institutional investment flow and stock returns using daily data over the period of January 1, 2002 to July 31, 2012. The analysis was conducted using two and three factors vector autoregression (VAR) frameworks, in which we considered investment flow of two sets of institutional investors, that is, foreign institutional investors (FIIs) and domestic institutional investors (DIIs) proxied by mutual funds, separately as well as jointly, to form the endogenous part in VAR. The analysis for each institutional investor group revealed that FIIs flow did not have any significant impact on market returns, but the DIIs investment flow did have a significant impact. We also found that the fund flow from both the investor groups was significantly affected by their own lags and lagged stock returns, implying that they followed their own past strategy as well as the recent market behaviour, albeit their trading strategy differed. Considering these two institutional investor groups jointly, we found that the net flow of FIIs and DIIs significantly influenced the Indian stock market even after controlling for market fundamentals. Furthermore, we found a feedback relationship between the institutional investment flow and stock market returns. Overall, it was found that the institutional investment collectively impacted the stock market returns.